2018
DOI: 10.20965/jdr.2018.p0897
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation on Earthquake-Resistance of Road Retaining Wall Using Gabion

Abstract: In the 2015 earthquake in Gorkha, Nepal, damaged different kinds of structures around the Kathmandu Basin. On the other hand, in mountainous areas, it was confirmed that gabion structures such as retaining walls along roads showed their high flexibility by performing their functions. In this paper, based on the results of the damage field survey on gabion retaining walls, a full-scale shake table test is conducted to evaluate the earthquake resistance of gabion retaining walls on roads, which are a common site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…A full-scale model experiment was conducted to verify the seismic performance and dynamic behavior of gabionbased retaining walls during an earthquake. This has been reported in detail by Nakazawa et al [6]. Based on the field survey findings, an experiment was carried out on a retaining wall model with a wall height of 3 m, using gabions with unit sizes of about 100 cm in width, height, and depth.…”
Section: Full-scale Shake Table Test Of Gabion Retaining Wallmentioning
confidence: 98%
See 1 more Smart Citation
“…A full-scale model experiment was conducted to verify the seismic performance and dynamic behavior of gabionbased retaining walls during an earthquake. This has been reported in detail by Nakazawa et al [6]. Based on the field survey findings, an experiment was carried out on a retaining wall model with a wall height of 3 m, using gabions with unit sizes of about 100 cm in width, height, and depth.…”
Section: Full-scale Shake Table Test Of Gabion Retaining Wallmentioning
confidence: 98%
“…In this set of experiments, tests were conducted using three gabion retaining wall types shown as Cases 1 to 3, one of which consisted of the vertically upright triple-stacked gabion retaining wall common in Nepal and two which involved newly proposed gabion structures [6]. As an example here, the model specifications and test results for Case 1, which show the vertically upright triple stacks common to Nepal, are shown in Figs.…”
Section: Full-scale Shake Table Test Of Gabion Retaining Wallmentioning
confidence: 99%
“…Hara et al (2018) conducted three field surveys, in July andNovember, 2015, andNo-vember, 2016, of the damage to the gabion road retaining walls along the Araniko Highway in the mountainous regions, and have previously reported the findings in detail. The usage of gabions reported by Hara et al (2018) and Nakazawa et al (2018), shown in Fig. 1, indicates that, of the 115 locations, 49%, or approximately half, were used as road retaining walls, followed by 19% as crash barriers.…”
Section: Previous Study On Gabion Structuresmentioning
confidence: 99%
“…Before shaing(Case1) Case1(257gal) Case2(313gal) Case3(302gal) Figure 1. Residual displacement of Gabion [8] confined pressure and 64kN/m 2 was fully considered. Figure 4 shows result of triaxial compressive test (CD test) of background and materials of support ground.…”
Section: Horizontal Displacement (Mm)mentioning
confidence: 99%
“…To evaluate the characteristics, and to grope more stable structures, the authors executed full-scale shake tests [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%